Direct synthesis of well-ordered mesoporous Al-SBA-15 and its correlation with the catalytic activity - Bhange, Pallavi; Bhange, Deu S.; Pradhan, Sivaram; Ramaswamy, Veda (Applied Catalysis A-General, 2011)
The synthesis of Al-SBA-15 under milder acidic conditions were made through an adjusting the molar H(2)O/HCl ratio which indicate the formation of Si-O-Al linkages that lead to isomorphous substitution of Si(4+) by some Al(3+) ions. By adjusting the H(2)O/HCl molar ratio, Al gets incorporated into the lattice of SBA-15, which is evidenced by XRD. N(2) adsorption, TEM, (29)Si and (27)Al MAS NMR spectroscopic data. Aluminium incorporated SBA-15 samples retained both structural and textural properties of SBA-15. The (27)Al MAS NMR confirms that a large proportion of the Al is inserted into tetrahedral positions within the framework. The Al(3+) ions could assume a tetrahedral coordination and be part of the hexagonal structure of silica in Al-SBA-15. In the present study, we have examined the effectiveness of Al-SBA-15, as an acid catalyst for the esterification of acetic acid and in benzylation of anisole. The high activity of Al-20 sample in esterification reaction has been attributed to isolated, generally tetrahedrally coordinated, framework Al species. While in benzylation of anisole, the best result was achieved with Al-5 catalyst. The selectivity for benzylanisole increases and that for dibenzylether decreases with increase in the Si/Al ratio of Al-SBA-15. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-SBA-15; Benzylation of anisole; Esterification of acetic acid